Comportamiento agronómico y valor nutricional del pasto mombasa (Panicum maximun cv.) con abonos orgánicos en diferentes estados de madurez en el campo experimental la playita UTC – La Maná - Conrado Palma, Carlos Alfonso (2015)
In the investigation of performance evaluation and nutritional value of organic fertilizers Mombasa grass at different maturity stage applied in the experimental field La Playita UTC. Had as specific objectives: determine the agronomic performance of Mombasa with manure crop in different maturity stage, compositional analysis to determine the nutritional value of the crop Mombasa with organic fertilizers at different maturity stage. Applied in the trial a Full Random Design (FRD) factorial arrangement, being the factor A (fertilizers) and factor B (cutting ages)....